Analisis Buku Bahasa Jerman Tingkat A1 pada Lektion “Freizeitbeschäftigung erzählen können” - Manik, Bertuah; Nainggolan, Ija Pebriana; Manalu, Elvrida Melvawati (Jurnal Dieksis ID, 2025)
This study examines the representation of leisure activities in the Super Deutsch textbook, specifically in the unit Lektion Freizeitbeschäftigung erzählen können, which is designed for learners of German as a foreign language at the A1 level. The urgency of this research arises from the need for teaching materials that not only meet linguistic standards but also reflect the social and cultural dynamics of learners, particularly in the Indonesian context. As a central tool in language education, textbooks play a crucial role in shaping students’ perceptions of language, culture, and social values. Therefore, a mismatch between the representations in textbooks and students' real-life experiences can negatively affect their learning motivation and engagement. This study aims to analyze how leisure activities, gender roles, and the influence of technology are represented in the unit, and to what extent the content is contextual and relevant to Generation Z learners in Indonesia. Using a qualitative content analysis approach that integrates discourse analysis, thematic analysis, and micro case studies, the study finds that although the textbook presents a range of linguistically appropriate activities for the A1 level, its content is not sufficiently aligned with students’ lived experiences. Gender representations tend to reinforce traditional stereotypes, and digital-era activities such as online gaming or social media use are absent. These findings underscore the importance of developing culturally responsive, inclusive, and up-to-date teaching materials. The study also offers pedagogical recommendations for educators and textbook developers to enhance student participation and foster intercultural communicative competence in foreign language learning in a more meaningful way.